Philosophy 167: Class 13 - Part 4 - Further Newton-Flamsteed Correspondence Concerning the 1680/1681 Comet: Flamsteed's Calculations of the Comet's Trajectory, and Newton's Response. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Flamsteed sent calculations of the two comets' trajectories to Newton, trying to prove they were the same orbit.; Opening line: "So Flamsteed gets this letter, defends himself at length."; Duration: 3:58 minutes.; Segment: Class 13, Part 4.